Femtosecond laser ablation of polystyrene: A molecular dynamics study. Issue 43 (30th July 2015) - Huang, Yanhua; Song, Chengwei; Zhang, Junjie; Sun, Tao
ABSTRACT In this work we perform molecular dynamics simulations to investigate the thermodynamic mechanisms of amorphous polystyrene ablated by a femtosecond laser pulse. The utilized width and fluence of the laser pulse are 10 fs and 1012 W/cm2, respectively. Furthermore, the effect of chain length on the microscopic material removal mechanisms and related macroscopic evolutions of system quantities is studied. Simulations results indicate that the ultra‐short laser pulse irradiation introduces significant instabilities into the target material because of the lattice perturbation, which leads to the relaxation of lattice destabilizations after the pulse through evaporation from the top surface and expansion within the bulk. It is found that the competition between the two mechanisms of evaporation and expansion is strongly influenced by the chain length. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42713.